Heat treatment of kieselguhr in order to improve filtration properties and for recycling - Ruß, Winfried; Schmid, Nicolaj; Meyer-Pittroff, Roland (BrewingScience, 2003)
The heat treatment for the recycling of used kieselguhr from deep bed filtration at 500 °C for 120 minutes in the presence of water vapor improves the filtration properties of the recycled kieselguhr. The cumulative increase in pressure across the filter bed of the pilot filter as a parameter for the maximum duration of filtration rose more gradually over time. The total amount of filtration time increases, therefore reducing filter down time. The turbidity, as a measure of filtration precision, does not increase. The water value and the permeability both increase with heat treatment. The particle size distribution indicates that structural changes were uncommon as a result of heat treatment. The specific surface area and the pore volume of the kieselguhr was reduced one third and the pore surface area, by 70 %. Additionally, the average pore diameter was almost doubled. The more decrease in filtration pressure, together with the higher values for turbidity both resulted from a change in pore size and a reduction in the adsorptive characteristics of the particles due to the heating process. Heat treatment presumably caused a reduction in smaller pores. Only the larger pores remained open, which lowered the resistance of the filter bed, increasing the flow rate through it. As a consequence, the filter bed compressed more slowly, which resulted in a more gradual pressure increase during filtration. Measuring the flow and the zeta potential, the amount of specific charge all prove that the adsorptive properties of the particles were reduced because of their diminished surface area and their reduction in surface area charge.